Cyanoprokaryota рек Полисарка, Пана, Варзуга (Мурманская обл., Россия) - Давыдов, Д.А. (Альгология, 2017)
Проведено изучение цианопрокариот вдоль речной системы рек Полисарка, Пана, Варзуга. На сегодняшний день флора цианопрокариот области насчитывает 359 видов и является одной из самых богатых в России. Выявлено 23 вида Cyanoprokaryota. Наиболее часто встречались Stigonema hormoides, S. informe, S. minutum, S. ocellatum. Приведен общий список собственных и литературных данных по видовому составу Cyanoprokaryota этого района. Типичные местообитания в пределах еловых, сосновых и березовых лесов не отличаются большим количеством видов цианопрокариот. Скальные сообщества Cyanoprokaryota лишены большого количества монтанных представителей, прежде всего из родов Gloeocapsa и Chroococcus, типичных для горных районов центральной части области. Отдельные локальные прибрежные местообитания могут обусловливать находки новых для региона видов, в частности нами были обнаружены Asterocapsa sp. и Microchaete sp. Paper presents new data on terrestrial Cyanoprokaryota revealed on the banks of the Polisarka, Pana, Varzuga rivers on the Kola Peninsula, Murmansk Region. The region is one of the most studied in Russia in terms of species composition of Cyanoprokaryota (359 species), but hard-to-reach central area of Kola Peninsula is still poorly investigated. In shore ecotopes and terrestrial habitats in the forest adjacent to the rivers, 23 taxa of Cyanoprokaryota were revealed. Poor species diversity in all studied communities is typical for this area. The most diverse species composition was on the rocks, both wet and dry. Stigonema hormoides (Kütz.) Bornet et Flahault, S. informe (Kütz.) Bornet et Flahault, S. minutum (C. Agardh) Hassall ex Bornet et Flahault, S. ocellatum (Dillwyn) Thur. ex Bornet et Flahault were the most common species in the investigated samples. In the birch, spruce and pine forests soil Cyanoprokaryota were rare and not abundant. Interesting records are Asterocapsa sp. and Microchaete sp. revealed together with other cyanobacteria, lichens and mosses on wet rocks. Generalized original and literature data on Cyanoprokaryota of the Polisarka, Pana, Varzuga rivers district are discussed.